Optimality and diversifiability of mean variance and arbitrage pricing portfolios - Mohammad Hashem Pesaran; Paolo Zaffaroni (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper investigates the limit properties of mean-variance (mv) and arbitrage pricing (ap) trading strategies using a general dynamic factor model, as the number of assets diverge to infinity. It extends the results obtained in the literature for the exact pricing case to two other cases of asymptotic no-arbitrage and the unconstrained pricing scenarios. The paper characterizes the asymptotic behaviour of the portfolio weights and establishes that in the non-exact pricing cases the ap and mv portfolio weights are asymptotically equivalent and, moreover, functionally independent of the factors conditional moments. By implication, the paper sheds light on a number of issues of interest such as the prevalence of short-selling, the number of dominant factors and the granularity property of the portfolio weights.
Keywords: C32; C52; C53; G11; 330; large portfolios; factor models; mean-variance portfolio; arbitrage pricing; market (beta) neutrality; well diversification; Portfolio-Management; Arbitrage Pricing; Varianzanalyse; Faktorenanalyse; Theorie